Dysferlinopathy: Spectrum of pathological changes in skeletal muscle tissue - N Gayathri; R Alefia; A Nalini; T C Yasha; M Anita; Vani Santosh; S K Shankar (Wolters Kluwer Medknow Publications, 2011)
Background: Dysferlinopathy is an autosomal recessive-limb girdle muscular dystrophy (AR-LGMD) caused due to the defect in gene encoding dysferlin, a sarcolemmal protein. Awareness of the variants and their relative frequency is essential for accurate diagnosis. Aim: To study the spectrum of morphologic changes in immunohistochemically proven cases of dysferlinopathies, to correlate the findings with clinical phenotype and durations of illness and determine the frequency. Materials and Methods: Dysferlinopathies seen over a period of 2 years at a tertiary neurological center were analyzed. Results: Clinically, majority had Miyoshi phenotype (46.6%) with distal involvement and LGMD phenotype (40%) with proximal muscle involvement. In addition, a proximo-distal and tibial muscle phenotype was encountered. Morphologically, rimmed vacuoles were noted in the Miyoshi phenotype. The presence of ragged red fibers, lobulated fibers and inflammation had no preference to a particular phenotype. Significant atrophy and lobulated fibers were noted in patients with longer duration of illness. Conclusions: Dysferlinopathy was the second most common identifiable cause (21%) of LGMD next to sarcoglycanopathies (27%).